PERSONNEL SELF-DEVELOPMENT IN THE MANAGEMENT SYSTEM OF AN INNOVATIVE AND ACTIVE ENTERPRISE - NYZHNYK, Viktor; BABCHYNSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article deals a question forming of self-development personnel in the conditions of knowledge economy. The scientific approaches concerning formation of the mechanism of management of development and use of personnel are considered. The analysis of scientific researches and publications concerning management of development and use of enterprise personnel is carried out. The paper emphasizes that the staff of an innovatively active enterprise is both a source of new ideas and a tool for their direct implementation in the practical activities of the enterprise. An essential condition for maintaining a stable positive economic dynamics of an innovatively active enterprise is staff development. The management system is the management of the enterprise, which exerts influence on the managed system in order to achieve the goals and objectives of the enterprise. Managed system – the staff of the enterprise, its quality characteristics, competencies, compliance with the needs of the enterprise and its development strategy. The target system includes strategic, tactical and operational goals and objectives, as well as criteria for selecting and evaluating the results of personnel development management of an innovatively active enterprise. The task of personnel development management of an innovatively active enterprise is to ensure compliance of quantitative and qualitative characteristics of personnel with the existing needs of the enterprise at the moment; development of innovative potential of the enterprise personnel. The innovative potential of an innovatively active enterprise should be understood as objective opportunities to maximize the intellectual potential of employees to achieve goals, as well as a set of tools, sources, opportunities and abilities, the use of which is aimed at solving any problems in innovation. The support system contributes to the realization of the goal of personnel development management of an innovatively active enterprise, by providing the necessary resources and creating the appropriate prerequisites.
Keywords: innovation-active enterprise; personnel development; innovation activity; personnel development management; self-development of personnel